The nexus between residential property prices, bank lending, construction output and interest rate: Policy lessons from Malaysia - Lim, Jia Hui; Lau, Wee Yeap (Universiti Putra Malaysia, 2018)
Using the aggregate and disaggregate dataset of various types of housing loan, this study examines the dynamic relationship between residential property prices, housing loan, construction output, and interest rate. Focusing on the aggregate data, it is noted that housing loan, construction output, and interest rate have significant and positive elasticities towards house prices in both short and long-term. The aggregate loan model indicates that about nine quarters or two years are required for full adjustment of house prices after experiencing a shock. Across the loan categories, first, the empirical analysis indicates that there is still a strong demand and potential opportunities for affordable properties. Second, homebuyers who purchase high-end properties will still borrow. Third, there is a significant and positive impact of interest rate on house prices in both short- and long-run, however, albeit a low percentage. The results of the error correction model imply the house prices for low-end housing loans take a longer period (8 to 10 percent quarterly) to return to equilibrium following a shock, compared to house prices for high-end housing loans (11 to 15 percent quarterly). The policymakers should review the housing policies by focusing more on low and the medium housing which is more affordable for the population.